The impact of deprivation on colorectal cancer‐stage distribution in a setting with high hospital bed density: A Japanese multilevel study - Toshiaki Shibata; Daisuke Shinjo; Kiyohide Fushimi (Cancer Medicine)
Abstract Background A methodology for determining the appropriate balance between medical access and combating poverty remains undetermined. To address the boundary conditions for exceedingly good medical access, this study examined whether the impact of deprivation on cancer stage distribution could be eliminated in Japan, which has the highest hospital bed density in the world. Methods A nationwide medical claims‐based database was used to evaluate the influence of municipality‐level hospital bed density and the postal code‐level areal deprivation index on cancer stage at diagnosis. Given the limited number of similar studies in Japan, we focused on colorectal cancer (CRC), for which disparities have been reported in a prefecture‐level study. Multilevel multivariate logistic regression models were used, with odds ratios (ORs) and 95% confidence intervals (CIs) adjusted for baseline and socioeconomic factors. Results Regardless of the early/advanced‐stage definitions, CRC consistently tended to be detected at more advanced stages in more deprived areas. In the analysis of stages 0–I/II–IV, the OR (95% CI) was 1.09 (1.05, 1.14) (p < 0.001). In the analyses of stages 0–I/II–IV and 0–II/III–IV, gradients were observed, and later detections were observed for more deprived segments. Hospital bed density was not significantly associated with the stage distribution. Conclusion The results indicate that inequalities in CRC detection due to deprivation persist even in the country with the highest hospital bed density worldwide, suggesting that poverty measures remain indispensable regardless of hospital bed access. Further investigation of various regions and cancers is required to develop a practical framework.